Holistic Writing Module Through Integrated Feedback: Analysis of Target Situation and Learning Need - Mubarok, Husni; Haryanto; Taufiqurrahman; Prayitno, Harun Joko; Fauzi, Shukor Sanim Mohd; Salaun, Clementine (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
It is crucial for advanced writing learning to have learning modules that allow students to cultivate holistic writing skills through a integrated feedback method. Nonetheless, the current modules do not include a thorough needs assessment, which restricts their applicability and efficiency. An examination of the teaching module, focused on the specific context and learning requirements, provides a thorough framework to facilitate advanced writing learning. This research analyzed the requirements of both lecturers and students concerning a holistic writing module that incorporates integrated feedback, focusing on the target situation (needs and lacks) and learning needs (preferences). The research employs the ADDIE development framework, with a focus on the analysis phase. Data were collected via questionnaires, interviews, and observations, and subsequently analyzed qualitatively using descriptive statistics. The findings revealed that the mean score for the need for the teaching module was 3.29, whereas the mean score for the lack of it was 2.72. This indicates a need for additional development of the teaching module. Learning observation results support this information, with an average score of 2.45, categorized as good. Students require a holistic writing module that incorporates integrated feedback. This research suggests that teaching modules for English Language Teaching (ELT) should be designed through a learner-centered and technology-supported approach to support advanced learning, innovative learning design, and contextual literacy development in higher education. Future research should involve developing and evaluating writing module to verify their efficacy.